Transformative Islamic Education from the Perspective KH Abdullah Munjul (Study of Manuscript Layang Siti Hasanah) - Zaimudin, Zaimudin; Ghofur, Abdul; Akbar, Meiza Fajar (Gema Wiralodra, 2024)
The "Layangan Siti Hasanah" manuscript, a significant Islamic text, provides valuable insights into historical educational practices. This research explores how its teachings can be applied to contemporary Islamic education to foster meaningful change and personal growth. The study involves a detailed analysis of the manuscript’s content, focusing on its educational methodologies and philosophies. It examines how these principles can be integrated into modern educational frameworks to enhance critical thinking, moral development, and holistic learning. Key findings reveal that the manuscript contains educational approaches that align with transformative educational goals. These approaches include methods for developing critical thinking and ethical understanding, which are relevant to current educational practices. The research suggests that incorporating these traditional principles into contemporary Islamic education can create a more dynamic and effective learning environment. By merging historical insights with modern needs, educators can promote both academic and personal development in students. Overall, this study highlights the importance of integrating traditional Islamic teachings with modern educational methods to achieve a transformative educational experience that benefits students in various aspects of their lives.The method used in this research is qualitative, while the approach used is the historical and anthropological approach to Islamic education, then the data collection techniques used are documentation and interviews and data analysis in the researcher's research using philological and symbiotic analysis. The results of research on Transformative Islamic education in the Layang Siti Hasanah manuscript according to KH Abdullah Munjul are divided into 3 domains of Transformation, namely: 1. Syariat teachings, 2. Tarekat teachings. 3. Marifat teaching.